Literarna veda in nacionalno ideološke težnje - Potocco, Marcello (Primerjalna književnost, 2007)
The author explains a possible context for tendencies in Canadian comparative literature to study literature as one of its discursive practices. The reason for this shift in Canada is found not only in the rise of poststructuralism, but also in the need to acknowledge Canadian cultural identity. The rise of multicultural studies may also be attributed to the need to shape the national myth, although cultural differences are now put forth as the unifying principle of this myth.
Keywords: comparative literature; primerjalna književnost; literarna veda; literary science; Canada; Kanada; multikulturnost; kulturna identiteta; kulturne študije